Pelatihan Pembuatan Company Profile Bagi Siswa SMK Gajah Mada - Damayanti Damayanti; Erliyan Redy Susanto; M. Ghufroni An'ars; Nirwana Hendrastuty; Wisnu Mukti Dwiyudho Putro; Fitrah Amalia Rahmadianti (Journal of Engineering and Information Technology for Community Service, 2023)
− Currently, digital information technology has an important role in all fields, including education. The existence of Information Technology makes it easy to carry out all activities in institutions and schools. Gajah Mada Vocational School is one of the schools in the Bandar Lampung region. Gajah Mada Vocational School in Bandar Lampung has a vision that is to want its graduates to become professionals who can be absorbed by the business and industrial world. This activity was carried out with the aim of providing knowledge and skills for students in making a company profile. The skills possessed are expected to become graduates who can channel knowledge and skills in making a company profile in the world of work